Performance of Midwives In Integrated Antenatal Services In Early Detecting High Risk Pregnancy in Kupang City - Gaspersz, Ani Agustini; Duarsa, Dyah Pradnyaparamita; Ani, Luh Seri (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The research method used an exploratory study design. Data were collected using in-depth interviews and direct observation. The research data were analyzed using thematic methods. The performance of midwives, seen from the input aspect, is lacking, where there is an additional workload for midwives, most of the midwives have not attended training, and there is a lack of examination room infrastructure. From the process aspect, there is lacking of supervision that more focus on early detection of high-risk pregnancies. The output aspect, the midwife's performance achievement was lacking in the two sample Puskesmas as seen from the coverage of each program indicator that had not yet reached the SPM target and the Kupang City Strategic Plan. It is necessary to increase the competence of midwives through integrated antenatal training and early detection of high-risk pregnancies that will support their performance achievement in ANC services